The effectiveness of the problem-based learning (PBL) model assisted by hypercontent e-books in improving students' critical thinking - Azrai, Eka Putri; Suryanda, Ade; Nurazizah, Meiza (Universitas Ahmad Dahlan, 2025)
Critical thinking has become a competency standard for primary and secondary education graduates. However, the quality of critical thinking among Indonesian students remains relatively low. Efforts are needed to enhance students' critical thinking skills. One such effort is implementing the problem-based learning (PBL) model assisted by hypercontent e-books based on cognitive conflict. This study aims to determine the effectiveness of the PBL model assisted by hypercontent e-books based on cognitive conflict in improving students' critical thinking abilities. The research uses a quasi-experimental method and was conducted at a high school in Jakarta. The sample consisted of 64 students, with 32 students in the experimental group and 32 students in the control group. The sample was selected using multistage random sampling. The results of the study show a significant improvement in critical thinking skills in the experimental group compared to the control group, with an average N-Gain of 0.61 for the experimental class, which is higher than the control class (0.45), with the effectiveness of learning falling within a range of 0.30-0.70, which is categorized as moderate. These results indicate the effectiveness of the PBL model assisted by hypercontent e-books based on cognitive conflict in enhancing students' critical thinking skills. The use of the PBL model assisted by hypercontent e-books based on cognitive conflict can be an innovative alternative in learning to improve students' critical thinking abilities.